The evaluation of student English activity (SEA) in Universitas Muhammadiyah Yogyakarta - Siti Afrianty H Kundji (Journal of English Language and Pedagogy, 2022)
This study aims to evaluate the organization of the Student English Activity (SEA). This organization made English its main component. The researcher showed the contribution of the context, input, and process. Then, the researchers explained the product of SEA. The researchers used the CIPP model in this study. The study took place in UMY and had participants from UMY. The participants were the stakeholder known as the president of SEA and the 10 members of SEA who were becoming the representative of all the members. The researchers collected the data from document analysis, observation, and interviews. The instruments from this study are documents, videos, and interview guidelines. The researcher used data condensation, data display, and conclusion drawing to analyze the data. The results o this study are all contributions of the CIPP to the SEA. the context role was to decide what to do to achieve the success of the SEA. The input contribution was to prepare a good facility, a qualified speaker or teacher, and preparation of the activities. The process contributions were the student's or members' enthusiasm and how they respond to the teacher in every activity. The process contribution also makes the students produce the language (English) confidently. With those parts, the member can achieve speaking skills, confidence, a good attitude, and intellectualism. These, the researchers call the result or product of SEA which the member has good speaking skills, confidence, good attitude, and intellectualism. Every aspect of CIPP has an important role to achieve the success of SEA. the context became the foundation of SEA, and the input and process became the core of the SEA. So SEA can get the product that same with the goals.